2007
DOI: 10.1038/labinvest.3700549
|View full text |Cite
|
Sign up to set email alerts
|

Renal p38 MAP kinase activity in experimental diabetes

Abstract: Renal cell activity of p38 mitogen-activated protein kinase (p38) is increased in the diabetic milieu. p38 mediates signals relevant for the development of diabetic nephropathy (DN). However, renal p38 in Type 1 diabetes in vivo, particularly in conditions reflecting the differences in metabolic control, and its activity in advanced stages of DN, has received less attention. We examined the p38 pathway in renal cortex of rats with streptozotocin diabetes (4 weeks) with poor (DS), moderate (DM), and intensive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 42 publications
(80 reference statements)
0
34
0
1
Order By: Relevance
“…p38 MAPK, a member of the MAPK family, is activated by physical and chemical stress factors, inflammatory cytokines, and both vasoactive and growth factors. 7 At the early stages of experimental diabetic nephropathy, active p38 has previously been localized in the JGA area 25,26 and in the distal tubules. 26 Consistent with these findings, immunohistochemistry showed that MD cells and adjacent portions of the distal nephron are the major sites of active p38 expression in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p38 MAPK, a member of the MAPK family, is activated by physical and chemical stress factors, inflammatory cytokines, and both vasoactive and growth factors. 7 At the early stages of experimental diabetic nephropathy, active p38 has previously been localized in the JGA area 25,26 and in the distal tubules. 26 Consistent with these findings, immunohistochemistry showed that MD cells and adjacent portions of the distal nephron are the major sites of active p38 expression in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…26 Consistent with these findings, immunohistochemistry showed that MD cells and adjacent portions of the distal nephron are the major sites of active p38 expression in the diabetic kidney. 7 Moreover, it has been found that ERK1/2 is generally but not exclusively responsive to activators of both receptor tyrosine kinases and G protein-coupled receptors. 27 In addition, succinate activated ERK in GPR91-transfected cells (293-hGPR91).…”
Section: Discussionmentioning
confidence: 99%
“…The diabetic kidney is stressed by multiple factors including hyperglycemia, reactive oxygen species, advanced glycation end products, proinflammatory cytokines, and angiotensin II-all of which can induce signaling via the p38 mitogen-activated protein kinase (MAPK) (2)(3)(4)(5). Increased activation of p38 MAPK in glomeruli and the tubulointerstitial compartment has been described in animal models of diabetic nephropathy as well as in patients with diabetic nephropathy (6)(7)(8)(9). Inhibition of p38 MAPK activation via pharmacologic and genetic approaches can suppress the induction of albuminuria, glomerular matrix expansion, and inflammation in models of type 1 and type 2 diabetic nephropathy (9,10), although intervention studies in established disease are lacking.…”
mentioning
confidence: 99%
“…Clinical trials have been shown the beneficial effects of intensive insulin therapy on diabetic microvascular complications [17][18]. Recent rodent study indicated that renal cortical p38 activity increased in diabetic rats but was attenuated by improved glycemic control achieved by insulin therapy [5]. However, that study was performed in type 1 diabetes rodent model and did not investigate the effects of late insulin therapy.…”
Section: Figmentioning
confidence: 75%
“…P38 MAPK was activated in vivo in glomeruli from diabetic rats and in vitro in mesangial cells exposed to high glucose [3][4]. Moreover, increased renal cortical p38 MAPK activity in diabetic rats could be attenuated by intensive (blood glucose=172 ± 10 mg/dL) but not poor or moderate metabolic control [5]. Therefore, attenuation of the p38 MAPK pathway in the renal cortex could be one beneficial effect of intensive insulin therapy.…”
mentioning
confidence: 84%